2018
DOI: 10.1016/j.cobeha.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Addiction and dopamine: sex differences and insights from studies of smoking

Abstract: Mesolimbic dopaminergic function influences addiction through effects on reinforcement learning, decision-making, and impulsivity. This review covers sex differences in dopaminergic neurochemistry, their hormonal and genetic determinants, and how differences in dopaminergic tone interact with sex and/or ovarian hormone status to affect cognitive functions. Findings from research on cigarette smoking reveal sex differences in striatal and midbrain dopamine D2-type receptor availability and striatal dopamine rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 137 publications
(125 reference statements)
1
3
0
Order By: Relevance
“…Additionally, they are more susceptible due to hormonal differences [36]. Several studies providing evidence of gender influence on the genetic-smoking relationship are available [9,11,35]. Interestingly, as association between the assessed SNPs and smoking was only observed for the homozygous variant genotypes, in accordance to other reports for European populations [28,32,37].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, they are more susceptible due to hormonal differences [36]. Several studies providing evidence of gender influence on the genetic-smoking relationship are available [9,11,35]. Interestingly, as association between the assessed SNPs and smoking was only observed for the homozygous variant genotypes, in accordance to other reports for European populations [28,32,37].…”
Section: Discussionsupporting
confidence: 80%
“…The same was noted for the CHRNA5 rs16969968 variant, only associated with increased risk of smoking in women. Some authors have suggested that women tend to evolve from experimentation to addiction more quickly and have greater difficulty in quitting smoking [34,35]. Additionally, they are more susceptible due to hormonal differences [36].…”
Section: Discussionmentioning
confidence: 99%
“…Time 1), and the smoking-by-sex interaction for each MRS metabolite level in the dACC, with age as a covariate. Sex was included as an independent variable based on a priori evidence of sex differences related to smoking [ 37 41 ] and of sex differences in metabolites irrespective of smoking [ 42 44 ]. The repeated measures testing assessed the reliability of the MRS scans and, in Smoking participants, detected any effects of breaking abstinence still evident 25–55 min after smoking.…”
Section: Discussionmentioning
confidence: 99%
“…While sex differences in the pervasiveness and prognosis of these disorders have long been known to exist, we still lack a complete understanding of why these differences emerge. Many of these disorders are characterized by dysfunction in the dopamine system in reward-related brain regions [3,4], and as such, there has been considerable interest in outlining the sex differences in dopaminergic anatomy, regulation, and function in preclinical models. Many sex differences exist independent of ovarian cycle fluctuations and reflect differences in basal dopamine system organization/neuroanatomy [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%